Individual and ‘national’ healthcare rights: Analysing the potential conflicts - Silva, Michael Da (Bioethics, 2021)
Individual rights to healthcare (RTHCs) are increasingly common in law. Yet even plausible theoretical defences thereof raise a classic problem in the philosophy of rights: How do individual rights relate to ‘collective’ rights within the same domain? Collective rights are common in international law and in the domestic laws of states that recognize RTHCs. These collective rights often include health-related components. There are at least prima facie plausible reasons to think that such collective ‘health rights’ should exist. A complete account of health rights should thus explain how individual and collective health rights claims relate to one another and what one should do in cases where the claims conflict. This work contributes to our understanding of health rights by analysing the relationship between individual RTHCs and a plausible candidate collective health right, namely a sub-state national right to control healthcare law and policy. It argues that concerns about rights conflicts in this context make sense, but genuine conflicts between individual health rights and national control over healthcare are rare. The strongest cases for sub-state national ‘self-determination’ rights do not implicate healthcare, or tend not to provide reasons to override any individual RTHCs. Conflicts are possible in rare cases and may even favour fulfilling the collective rights claims. Yet individual RTHCs remain important even in those cases. Individual rights remain useful measures for evaluating the exercise of collective rights: exercises that violate (or even fail to fulfil) individual health rights are worse for so doing.